2006
DOI: 10.1590/s0036-36342006000800006
|View full text |Cite
|
Sign up to set email alerts
|

Entre la negación y la impotencia: prestadores de servicios de salud ante la violencia contra las mujeres en México

Abstract: Health care providers were categorized based on the extent to which they reproduced four"discourses about violence". These discourses influence their daily practice and are related to the informants' gender values and social positions. Most informants expressed their willingness to address the issue of domestic violence. CONCLUSIONS. Attention to and care for domestic violence is insufficient in health services; this may be due more closely related to a predominant discourse tolerating domestic violence among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
2
0
8
Order By: Relevance
“…This was particularly true among staff at lower levels of hospital care, particularly where they had scarce resources, lack of local support services and limited access to training on IPV. Studies from other fields of health care also reported how some providers find offering emotional care to patients more difficult than any other aspects of clinical care [26,48]. The medicalised approach focuses mainly on the physical aspects of abuse and cannot help resolve women’s problem in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was particularly true among staff at lower levels of hospital care, particularly where they had scarce resources, lack of local support services and limited access to training on IPV. Studies from other fields of health care also reported how some providers find offering emotional care to patients more difficult than any other aspects of clinical care [26,48]. The medicalised approach focuses mainly on the physical aspects of abuse and cannot help resolve women’s problem in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that their judgmental and directive attitudes and their lack of knowledge represent a major obstacle for abused women, often resulting in low disclosure [14-18]. Misconceptions and stereotypes around IPV are present among many clinicians, who may feel that violence is normal, who may hold negative views about providing services for IPV, or think that women are to blame for their husband’s aggression, [2,19-25], or who seem to be more focused on physical illness [7,26]. Health care providers’ clinical responses are shaped by own personal experiences and socio-cultural beliefs [27].…”
Section: Introductionmentioning
confidence: 99%
“…Los tipos resultantes fueron: (1) discurso dominante basado en estereotipos rígidos de género; (2) anti-violencia basado en valores tradicionales de género; (3) anti-violencia basado en ideas sobre "lo moderno"; y (4) anti-violencia basado en los derechos de la mujer. Para un análisis de esta tipología nos remitimos a Herrera et al 12 .…”
Section: Resultsunclassified
“…Diversas medidas vêm sendo tomadas nos últimos anos com o intuito de combater esse problema, que tem um impacto cada vez maior na vida da população. Como já foi citado anteriormente, conferências, declarações e convenções vem sendo realizadas nacional e internacionalmente, em busca de soluções para coibir as práticas de violência de gênero (HERRERA, 2006;MARTIN, 2003;RODRIGUES-BOLAÑOS et al, 2005).…”
Section: A Violência De Gênero Como Uma Questão De Saúdeunclassified
“…Há questões macro e micro-sociais que explicam as dificuldades de percepção e atenção à violência, tais como fatores pessoais e aspectos culturais e sociais derivados do sistema de gênero dominante e das representações sociais a isso vinculadas (HERRERA et al, 2006). Os profissionais de saúde são, antes de tudo, pessoas que compartilham os mesmos valores culturais e, às vezes vivem os mesmo níveis de violência daqueles a quem devem tratar e dar apoio.…”
Section: Os Tipos De Violência E Sua Gravidadeunclassified